Sovereigns, Upstream Capital Flows and Global Imbalances - Laura Alfaro; Sebnem Kalemli-Ozcan; Vadym Volosovych (Tinbergen Institute, 2011)
We decompose capital flows – both debt and equity – into public and private components and study their relationship with productivity growth. This exercise reveals that international capital flows are mainly shaped by government decisions and sovereign to sovereign transactions. Specifically, we show: (i) international capital flows net of government debt are positively correlated with growth and allocated according to the neoclassical predictions; (ii) international capital flows net of official aid flows, which are mostly accounted as debt, are also positively correlated with productivity growth consistent with the predictions of the neoclassical model; (iii) public debt flows are negatively correlated with growth only if government debt is financed by another sovereign and not by private lenders. Our results show that the failure to consider official flows as the main driver of uphill flows and global imbalances is an important shortcoming of the recent literature.
urn:NBN:nl:ui:15-1765/26087
Keywords: F21; F41; O1; 330; current account; aid/government debt; reserves; puzzles of flows; productivity; Kapitalmobilität; Produktivität; Politische Entscheidung